2016
DOI: 10.6023/cjoc201605046
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Chemistry of Keteniminium Salts

Abstract: Keteniminium salts are unique heteroallenes. The high electrophility and cumulative double bonds render them versatile reactivity. This paper describes the keteniminium salts formed by electrophilic activation of amides or ynamides with non-metal electrophilic reagents. These keteniminium salts mainly undergo electrophilic addition, eletrophilic substitution, cycloaddition with various nucleophiles. In past few years, the study of keteniminium induced electrophilic rearrangement has progressed rapidly. The new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…[14] Much less explored but equallyp romising is the anionic activation of ynamides to generate ketenimines, [15] usually through ar eaction at the electron-withdrawing group under basic conditions. [14] Much less explored but equallyp romising is the anionic activation of ynamides to generate ketenimines, [15] usually through ar eaction at the electron-withdrawing group under basic conditions.…”
Section: Base-mediated Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Much less explored but equallyp romising is the anionic activation of ynamides to generate ketenimines, [15] usually through ar eaction at the electron-withdrawing group under basic conditions. [14] Much less explored but equallyp romising is the anionic activation of ynamides to generate ketenimines, [15] usually through ar eaction at the electron-withdrawing group under basic conditions.…”
Section: Base-mediated Transformationsmentioning
confidence: 99%
“…Acidic or electrophilica ctivation of ynamides can give birth to keteniminiumi ons, which have recently witnessed as urge in attention by the synthetic community due to their high electrophilicity and broad reactivity. [14] Much less explored but equallyp romising is the anionic activation of ynamides to generate ketenimines, [15] usually through ar eaction at the electron-withdrawing group under basic conditions. Evano's group developede fficient procedures to access ynimines, ap articularc lass of ynamides for which the stability is provided by the imino substituent;subsequently the group explored their unusualr eactivity.T hey showed that adding an organolithium on ynimine 47 generates ynamide/ketenimine lithium anion 48/49 (Scheme17), which can then evolve following three distinct reaction pathways.…”
Section: Base-mediated Transformationsmentioning
confidence: 99%
“…Despite that their first preparation was accomplished by Viehe and coworkers half a century ago, 1 the extensive utility of ynamides in organic synthesis has been realized only recently and the field continues to stimulate high research interest. Ynamides can serve as precursors of keteniminium salts 2 and α-imino-metal carbenes, 3 and pave the foundation for a number of novel ynamide-mediated addition reactions, 4 annulation (cycloaddition and cycloisomerization) reactions, 5 metal-catalyzed cross-coupling reactions, 6 and free radical reactions. 7 In addition, useful synthetic reagents can be designed based on the unique reactivity of ynamides, as demonstrated recently by Zhao's group with their efficient and mild racemization-free coupling reagents for the synthesis of amides and peptides.…”
Section: Introductionmentioning
confidence: 99%